Periodontal emergencies in patients from the North Area. Sancti Spíritus - Ileana María Yero Mier; Bertha de la Caridad González Fortes; Yanela Martinez Jimenez; Yoagny Andres Rodriguez Rosado; Leobel Morell Pérez (Gaceta Médica Espirituana)
Background: Periodontal emergencies are characterized by being painful, sudden and of short duration, requiring dental emergency services.